Ab Initio Study of Carbon Nanotube Transistor-Based Gas Sensor for NO2 Detection - Sivasathya, S.; John Thiruvadigal*, D. (Asian Journal of Chemistry, 2013)
Continuous monitoring and detection of atmospheric gases are important for assessment considering the potential health risks involved. The unique characteristics of carbon nanotubes due to their hollow center, nanometer size and large surface area changes their electrical resistance when exposed gases at room temperature making them applicable for sensors. In this paper, we investigate the potential application of carbon nanotubes as a NO2 gas sensor by measuring the change of electrical resistance of the carbon nanotubes upon gas absorption and the surface of the single wall carbon nanotube channel in a carbon nanotube field effect transistor device. Our approach is based on first-principle density functional theory to compute equilibrium structures and electronic density of states. Here, the reaction between NO2 and single wall carbon nanotube is simulated which leads to the changes in transport properties and I-V curve of carbon nanotube field effect transistor.